Combining Literature Review With a Ground Truth Approach for Diagnosing Huntington's Disease Phenocopy - Nguyen, Quang Tuan Rémy; Ortigoza Escobar, Juan Dario; Burgunder, Jean-Marc; Mariotti, Caterina; Saft, Carsten; Hjermind, Lena Elisabeth; Youssov, Katia; Landwehrmeyer, G. Bernhard; Bachoud-Lévi, Anne-Catherine (Frontiers in Neurology, 2022)
One percent of patients with a Huntington’s disease (HD) phenotype do not have the huntingtin (HTT) gene mutation. These are known as HD phenocopies. Their diagnosis is still a challenge. Our objective is to provide a diagnostic approach to HD phenocopies based on medical expertise and a review of the literature. We employed two complementary approaches sequentially: a review of the literature and two surveys analyzing the daily clinical practice of physicians who are experts in movement disorders. The review of the literature was conducted from 1993 to 2020, by extracting articles about chorea or HD-like disorders from the database Pubmed, yielding 51 articles, and analyzing 20 articles in depth to establish the surveys. Twenty-eight physicians responded to the first survey exploring the red flags suggestive of specific disease entities. Thirty-three physicians completed the second survey which asked for the classification of paraclinical tests according to their diagnostic significance. The analysis of the results of the second survey used four different clustering algorithms and the density-based clustering algorithm DBSCAN to classify the paraclinical tests into 1st, 2nd, and 3rd-line recommendations. In addition, we included suggestions from members of the European Reference Network-Rare Neurological Diseases (ERN-RND Chorea & Huntington disease group). Finally, we propose guidance that integrate the detection of clinical red flags with a classification of paraclinical testing options to improve the diagnosis of HD phenocopies.